Nuclear accidents on policy: Notes on public perception - Felix Richter; Malte Steenbeck; Markus Wilhelm (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2012)
Nuclear energy is controversially discussed in many countries. Major nuclear accidents as recently in Fukushima set nuclear power plant security on top of the public agenda and increase pressure on policy makers to provide adequate reactions. Using data of the German Socio-economic Panel we analyze the effects of the accident in Fukushima and the following resolution on a nuclear phase-out plan by the German federal government on subjective perceptions using ordinary least squares and ordered logit estimates. We find strong evidence that the period after Fukushima increases the probability to report greater worries about the environment. Furthermore, we find evidence for an increase in reported levels of happiness and a decrease in the probability to be very worried about the security of nuclear power plants after the government's resolution on the nuclear phase-out.
Keywords: I31; N70; Q48; 330; nuclear energy; nuclear accident; Fukushima; phase-out plan; life satisfaction; environment